The industrial heritage and post-industrial urban identity: the case of Lodz in Poland - Sowińska-Heim, Julia (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2020)
This article examines how the concept of redefinition of city identity is connected and merges with activities concerning adaptive reuse of the 19th-century post-industrial architectural heritage of Lodz, one of largest Polish cities.